Nanophotonic Devices for Linear and Nonlinear Optical Signal Processing - Koos, Christian (Karlsruhe Series in Photonics & Communications / Universität Karlsruhe (TH), Institute of High-Frequency and Quantum Electronics (IHQ), 2007)
High index-contrast nanophotonic devices are key components for future board-to-board and chip-to-chip optical interconnects: The strong confinement of light enables dense integration, and nonlinear effects can be exploited at low power levels. Cheap large-scale production is possible by using highly parallel microfabrication techniques, and semiconductor-based nanophotonic devices can be integrated together with electronic circuitry on a common chip. Particularly intense research is carried out to realise optical devices on silicon substrates, using mature complementary metal-oxide-semiconductor (CMOS) fabrication techniques.This book discusses the modelling, fabrication and characterization of linear and nonlinear nanophotonic devices. Roughness-related scattering loss in high index-contrast waveguides is investigated both theoretically and experimentally, and methods of loss reduction are developed. Novel silicon-based devices for electro-optic modulation and for all-optical signal processing are presented. Nonlinear dynamics in active quantum-dot devices are studied, and resonant field enhancement is exploited to improve the efficiency of nonlinear interaction.